2016
DOI: 10.11159/awspt16.111
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Evaluating the Performance of a Wastewater Treatment Plant

Abstract: -The main concept of wastewater treatment is to remove or reduce the excessive amounts of contaminants from the wastewater. This performance study was needed to evaluate the efficiency of a wastewater treatment plant in decreasing the pollutants level, to meet with the governmental environmental standards. Also, the wastewater re-use for irrigation approaches must be in accordance with the criteria along with indicators should be monitored also impended up on a complying basis, and necessity at the stage of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…The treatment results (Tables 1-2) were assessed by measuring several parameters (pH, turbidity, BOD 5 , COD). These parameters were normally adopted elsewhere [28] when assessing the performance of such wastewater treatment scheme. It can be observed that a slight reduction on pH values (<5%) occurred, in general, due to plasma treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment results (Tables 1-2) were assessed by measuring several parameters (pH, turbidity, BOD 5 , COD). These parameters were normally adopted elsewhere [28] when assessing the performance of such wastewater treatment scheme. It can be observed that a slight reduction on pH values (<5%) occurred, in general, due to plasma treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Gambar 1. Lumpur yang terbentuk di IPAL Komunal Domestik Kampung Kandang Evaluasi fungsi eksisting dari IPAL diperlukan untuk menilai performa dari unit pengolahan dan air buangan akhir sudah sesuai kriteria standar baku mutu atau sudah memerlukan tingkat pengolahan yang lebih tinggi (US Environmental Protection Agency, 1974;Hegazy and Gawad, 2016). Indikator yang diperlukan dalam evaluasi limbah cair salah satunya adalah perhitungan efisiensi penyisihan yang harus dicapai oleh IPAL (Vítez et al, 2012).…”
Section: Pendahuluanunclassified
“…Wastewater is universally labeled as domestic wastewater or industrial wastewater. Domestic wastewater refers to wastewater spawn from nonmanufacturing activities routine in inhabited homes which include sewage (from toilets) and grey water (from bathrooms and kitchens) (Mohamed and Mohamed, 2016). It comprises of human waste (enclosing pathogens), paper, soap, detergent filtrate and food oddments (MEIDW, 2018).…”
Section: Introductionmentioning
confidence: 99%